STATUS OF LIPID PEROXIDATION AND TOTAL ANTIOXIDANT CAPACITY IN REGULAR VOLUNTARY BLOOD DONORS - Chandrika; Kumari, Suchetha; K., Jayaprakash Shetty; Kathyayani; V., Sharada (Journal of Health and Allied Sciences NU, 2011)
Oxygen free radicals and products of oxidative cell damage are known as biomarkers that escalate in the pathophysiology of many diseases. The aim of this study is to evaluate association between blood donation and total antioxidant capacity and lipid peroxidation product malondialdehyde(MDA). The levels of MDA and total antioxidant capacity(TAC) were studied in serum of 90 male voluntary blood donors aged from 20 to 45 years attending K. S. Hegde charitable hospital, Blood bank, for determination of lipid peroxidation and antioxidant status, respectively. The donors were divided into nine groups depending on number of blood donation. With increase in number of blood donation the serum MDA level were significantly reduced (p>0.01) but total antioxidant activity was significantly increased (p>0.01). High frequency of blood donors had evidence of decreased lipid peroxidation and enhanced activity of total antioxidants when compared with low frequency blood donors. which can be considered as one of the fringe benefits of regular blood donation.
Keywords: Blood donation; lipid peroxidation; malondiadehyde; total antioxidant capacity